Effectiveness Of Psychosocial Support Programs In Reducing Burnout And Stress Among Nursing Staff: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Burnout and stress among nurses are pervasive global issues, undermining both workforce sustainability and patient care quality. Psychosocial support programs—including mindfulness, yoga, empowerment, and training interventions—are increasingly implemented to enhance resilience and mitigate occupational stress.Objectives: This review aimed to synthesize empirical evidence on the effectiveness of psychosocial interventions in reducing stress, burnout, and related outcomes among nursing staff across diverse clinical and cultural contexts.Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. Eligible studies included randomized controlled trials, quasi-experimental designs, cross-sectional surveys, and meta-analyses published between 2009 and 2025. The final analysis included 22 primary intervention studies and 8 systematic reviews/meta-analyses. Data were extracted on study design, population, interventions, measurement tools, and outcomes. Quality was assessed using the Cochrane Risk of Bias Tool and Newcastle-Ottawa Scale.Results: Psychosocial interventions demonstrated significant reductions in emotional exhaustion, depersonalization, stress, and anxiety across most studies. Mindfulness-based interventions consistently improved resilience and reduced burnout, yoga programs reduced stress and normalized physiological indicators, and empowerment programs enhanced professional identity and satisfaction. Training programs improved knowledge, self-efficacy, and coping skills. Context-specific interventions during crises such as COVID-19 were particularly effective in addressing acute stressors.Conclusions: Psychosocial support programs are effective, adaptable strategies for reducing stress and burnout among nursing staff. Multi-component interventions that combine individual-focused practices with organizational-level strategies offer the greatest potential for sustainable improvements in nurse well-being and patient care outcomes.